Modeling and preliminary experimental results of thin film heating during the passage of a high-energy electron beam - Luhanko, M.; Shopen, O.; Karpus, S.; Malykhina, T. (Problems of Atomic Science and Technology, 2023)
The preliminary experimental results as well as modeling the heating of thin-foil materials during the passage of high-energy electrons with energy of 15 MeV are presented. Foils of 50 μm titanium, 50 μm aluminum and 125 μm Kapton® were chosen as the test targets. A calculation technique has been developed, which consists of automating the finite difference method applying Python programming language tools. These tools allowed solving the problem of heat distribution in the thin foil, taking into account the ionization losses of the primary electron beam and the black body radiation. The data on the surface temperature distribution of the research samples were obtained. The time for establishing thermal equilibrium was determined taking into account the distribution of the electron beam current density. It is shown that optimization of the main parameters of the high-energy electron beam beam (for example the current density) makes it possible to neglect the thermal loads on these films, which was confirmed during bench tests at 30 MeV electron accelerator of the IHEPNP NSC KIPT. Представлено попередні експериментальні результати та результати моделювання нагріву тонких плівок з титану товщиною 50 мкм, алюмінію товщиною 50 мкм та Каптону® товщиною 125 мкм при проходженні крізь них високоенергетичних електронів з енергією 15 МеВ. Струм пучка електронів дорівнював 1 мкА. Розроблено методику розрахунків, що полягає в автоматизації методу скінченних різниць за допомогою засобів мови програмування Python, що полягає у вирішенні задачі розповсюдження тепла у плівці з урахуванням гальмівних втрат первинного пучка електронів та випромінювання абсолютно чорного тіла. Отримано дані з розподілу температури по поверхні зразків та визначено час встановлення теплової рівноваги з урахуванням розподілу густини струму пучка електронів. Показано, що оптимізація важливих параметрів пучка високоенергетичних електронів, а саме, густини струму пучка, дає змогу знехтувати тепловими навантаженнями на дослідні зразки зазначених плівок, що підтверджено під час стендових випробувань на лінійному прискорювачі електронів ІФВЕЯФ ННЦ ХФТІ з енергією до 30 МеВ.